If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=20-3b
We move all terms to the left:
2-(20-3b)=0
We add all the numbers together, and all the variables
-(-3b+20)+2=0
We get rid of parentheses
3b-20+2=0
We add all the numbers together, and all the variables
3b-18=0
We move all terms containing b to the left, all other terms to the right
3b=18
b=18/3
b=6
| 6(5b-4)=-3(8+4b) | | 16=g/3+12 | | 2n+6+n+2=6(n-1)-7(3n-2) | | -2(-7x+8)=3(5x-1)-2x | | 3(4n-1)-1=-8(-2n-1) | | n-6+2n-8=7(3n+1)+3(-8n+1) | | 4(2x+7)+2x=-1+3(1-x) | | 6(p+2)-(7p-2)=-7p-p | | -5(n+2)=-2(3n+7)-7 | | 4x+67=143 | | 5-6x=x+15 | | 8(2x-2)=4(3x-7) | | -6(r+2)+6=-8(r+2) | | 224=-16t2+144t | | -2(v+4)=-8(v+4) | | 7(2x+1)=3(x+2) | | 7(2x+1)=3(x+2 | | c=50*100 | | 2w+1/2=3/2 | | 4103-29=d | | 2w=1/3 | | 274+37=b | | 120/4=z | | 57*21=a | | (7t-2)-(3t1)=-3(1-3t) | | (7t-2)-(3t1)=-3(1-3t | | 3.4x=5.1 | | 0=-4.9t^2+19.6t+1 | | 2=-4.9t^2+19.6t+1 | | 3u-(-1)=7 | | -2(2s-5)-10=-3(3s+5)-3 | | -3(3s-1)-3=-3(6s+6)-3 |